2017
DOI: 10.2147/jpr.s140925
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin 8% patch treatment for amputation stump and phantom limb pain: a clinical and functional MRI study

Abstract: PurposeThe aim of this study was to measure the efficacy of a single 60 min application of capsaicin 8% patch in reducing chronic amputation stump and phantom limb pain, associated hypersensitivity with quantitative sensory testing, and changes in brain cortical maps using functional MRI (fMRI) scans.MethodsA capsaicin 8% patch (Qutenza) treatment study was conducted on 14 patients with single limb amputation, who reported pain intensity on the Numerical Pain Rating Scale ≥4/10 for chronic stump or phantom lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 89 publications
2
18
0
Order By: Relevance
“…We also summarized whether they monitored and reported adverse events caused by the treatments for chronic pain. Among 75 studies, we found that 12 studies monitored and reported treatment-related adverse events (Walitt et al, 2007 ; Gustin et al, 2010 ; Tillisch et al, 2012 ; Petzke et al, 2013 ; Boyer et al, 2014 ; Li et al, 2015 ; Zhao et al, 2015 , 2018 ; Zhang et al, 2016 ; Pinto-Sanchez et al, 2017 ; Privitera et al, 2017 ; Tetreault et al, 2018 ), and 7 studies monitored but did not report adverse events in the articles (Harris et al, 2013 ; Taylor et al, 2013 ; Jensen K. B. et al, 2014 ; Flodin et al, 2015 ; Sanders et al, 2015 ; Geha et al, 2016 ; Rogachov et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also summarized whether they monitored and reported adverse events caused by the treatments for chronic pain. Among 75 studies, we found that 12 studies monitored and reported treatment-related adverse events (Walitt et al, 2007 ; Gustin et al, 2010 ; Tillisch et al, 2012 ; Petzke et al, 2013 ; Boyer et al, 2014 ; Li et al, 2015 ; Zhao et al, 2015 , 2018 ; Zhang et al, 2016 ; Pinto-Sanchez et al, 2017 ; Privitera et al, 2017 ; Tetreault et al, 2018 ), and 7 studies monitored but did not report adverse events in the articles (Harris et al, 2013 ; Taylor et al, 2013 ; Jensen K. B. et al, 2014 ; Flodin et al, 2015 ; Sanders et al, 2015 ; Geha et al, 2016 ; Rogachov et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study involved hospital visits and telephone calls, as shown in Figure 1. Patients attended the hospital unit for study visits 1 to 3, and the application of the capsaicin 8% patches was carried out in the hospital as previously described in detail, with illustrations 67. The capsaicin 8% patches covered the feet and distal calf, including the region of the pretreatment baseline skin biopsies, after they had fully healed.…”
Section: Methodsmentioning
confidence: 99%
“…Capsaicin is an agonist which acts on TRPV1, the heat and capsaicin receptor, and recent advances in the understanding of its mechanism and site of action have been reviewed 66. Our recent study showed its effect and mechanisms in amputation stump pain and phantom limb syndrome 67…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic efficacy of the high-concentration 8% capsaicin dermal patch for the treatment of PNP has been assessed in patients with PDPN and in nondiabetic patients with PNP of various etiologies, including PHN and HIV-AN, both in large, randomized clinical trials (Tables 1 and 2) [35][36][37][38][39][40][41][42][43][44][45][46][47], and in 'fieldpractice' experiences (Tables 3-6) [8,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Therapeutic Efficacy Of the Capsaicin 8% Dermal Patchmentioning
confidence: 99%
“…d Mean change from baseline to week 2 [56], week 4 [51], week 8 [53], and week 52 [68]. If not otherwise specified: mean change in pain score from baseline to week 2 [49]; weeks 2-8 [53]; weeks 2-12 [55,56,58,61,62,; week 4 [51]; week 8 [54]; week 12 [59,63], and month 6 [68].…”
Section: Therapeutic Efficacy Of the Capsaicin 8% Dermal Patchmentioning
confidence: 99%